-
Notifications
You must be signed in to change notification settings - Fork 38
Commit
This commit does not belong to any branch on this repository, and may belong to a fork outside of the repository.
- Loading branch information
Showing
1 changed file
with
59 additions
and
1 deletion.
There are no files selected for viewing
This file contains bidirectional Unicode text that may be interpreted or compiled differently than what appears below. To review, open the file in an editor that reveals hidden Unicode characters.
Learn more about bidirectional Unicode characters
Original file line number | Diff line number | Diff line change |
---|---|---|
@@ -1 +1,59 @@ | ||
\workinprogress % TODO | ||
\starred | ||
The statement can be included into Lemma 4.3 as an extension to case~2: | ||
\begin{enumerate}[start=2,label=\arabic*$'$.] | ||
\item If $f(n)=\Theta(n^{\log_ba}/\lg n)$, then $g(n)=\Theta(n^{\log_ba}\lg\lg n)$. | ||
\end{enumerate} | ||
We'll prove it similarly as the original case~2. | ||
|
||
Since $f(n)=\Theta(n^{\log_ba}/\lg n)$, we have that $f(n/b^j)=\Theta((n/b^j)^{\log_ba}/\lg(n/b^j))$. | ||
However, to avoid zero from appearing in the denominator, in equation (4.19) we'll substitute the equivalent bound $f(n/b^j)=\Theta((n/b^j)^{\log_ba}/\lg(n/b^{j-1}))$, since $b>1$ is a constant: | ||
\begin{align*} | ||
g(n) &= \sum_{j=0}^{\lfloor\log_bn\rfloor}a^j\Theta\left(\left(\frac{n}{b^j}\right)^{\log_ba}\!\!\Bigm/\lg\left(\frac{n}{b^{j-1}}\right)\right) \\ | ||
&= \Theta\left(\sum_{j=0}^{\lfloor\log_bn\rfloor}a^j\left(\frac{n}{b^j}\right)^{\log_ba}\!\!\Bigm/\lg\left(\frac{n}{b^{j-1}}\right)\right) && \text{(by \refProblem{3-5}(c), repeatedly)} \\ | ||
&= \Theta\left(n^{\log_ba}\sum_{j=0}^{\lfloor\log_bn\rfloor}\frac{a^j}{b^{j\log_ba}\lg(n/b^{j-1})}\right) \\ | ||
&= \Theta\left(n^{\log_ba}\sum_{j=0}^{\lfloor\log_bn\rfloor}\frac{1}{\lg(n/b^{j-1})}\right) && \text{(by equation (3.21))} \\ | ||
&= \Theta\left(n^{\log_ba}\sum_{j=0}^{\lfloor\log_bn\rfloor}\frac{\log_b2}{\log_b(n/b^{j-1})}\right) && \text{(by equation (3.19))} \\ | ||
&= \Theta\left(n^{\log_ba}\log_b2\sum_{j=0}^{\lfloor\log_bn\rfloor}\frac{1}{\log_bn-(j-1)}\right) && \text{(by equations (3.18) and (3.20))} \\ | ||
&= \Theta\left(n^{\log_ba}\sum_{j=0}^{\lfloor\log_bn\rfloor}\frac{1}{\log_bn-j+1}\right) && \text{($\log_b2>0$ is a constant)}. | ||
\end{align*} | ||
The summation within the $\Theta$-notation can be bounded from above as follows: | ||
\begin{align*} | ||
\sum_{j=0}^{\lfloor\log_bn\rfloor}\frac{1}{\log_bn-j+1} &\le \sum_{j=0}^{\lfloor\log_bn\rfloor}\frac{1}{\lfloor\log_bn\rfloor-j+1} \\ | ||
&= \sum_{j=1}^{\lfloor\log_bn\rfloor+1}\frac{1}{j} && \text{(reindexing)} \\ | ||
&= \ln(\lfloor\log_bn\rfloor+1)+O(1) && \text{(by equation (A.9))} \\ | ||
&\le \ln(2\log_bn)+O(1) && \text{(as long as $n\ge b$)} \\ | ||
&= \frac{\lg(\lg n/\lg b)}{\lg e}+\ln2+O(1) && \begin{minipage}{1.5in}(by equations (3.18)\\\null\quad and (3.19) (twice))\end{minipage} \\ | ||
&= \frac{\lg\lg n}{\lg e}-\frac{\lg\lg b}{\lg e}+\ln2+O(1) && \begin{minipage}{1.5in}(by equations (3.18)\\\null\quad and (3.20))\end{minipage} \\ | ||
&= O(\lg\lg n) && \text{(after ignoring constants)}, | ||
\end{align*} | ||
and from below as follows: | ||
\begin{align*} | ||
\sum_{j=0}^{\lfloor\log_bn\rfloor}\frac{1}{\log_bn-j+1} &\ge \sum_{j=0}^{\lfloor\log_bn\rfloor}\frac{1}{\lfloor\log_bn\rfloor+1-j+1} \\ | ||
&= \sum_{j=2}^{\lfloor\log_bn\rfloor+2}\frac{1}{j} && \text{(reindexing)} \\ | ||
&= \left(\sum_{j=1}^{\lfloor\log_bn\rfloor+2}\frac{1}{j}\right)-1 \\ | ||
&= \ln(\lfloor\log_bn\rfloor+2)+O(1)-1 && \text{(by equation (A.9))} \\ | ||
&> \ln(\log_bn)+O(1)-1 \\ | ||
&= \frac{\lg(\lg n/\lg b)}{\lg e}+O(1)-1 && \text{(by equation (3.19) (twice))} \\ | ||
&= \frac{\lg\lg n}{\lg e}-\frac{\lg\lg b}{\lg e}+O(1)-1 && \begin{minipage}{1.5in}(by equations (3.18)\\\null\quad and (3.20))\end{minipage} \\ | ||
&= \Omega(\lg\lg n) && \text{(after ignoring constants)}. | ||
\end{align*} | ||
Hence, we can conclude that $g(n)=\Theta(n^{\log_ba}\lg\lg n)$, thereby completing the proof of case 2$'$ of Lemma~4.3. | ||
|
||
In a similar fashion we can define an extension to case~2 in Theorem~4.4: | ||
\begin{enumerate}[start=2,label=\arabic*$'$.] | ||
\item If $f(n)=\Theta(n^{\log_ba}/\lg n)$, then $T(n)=\Theta(n^{\log_ba}\lg\lg n)$. | ||
\end{enumerate} | ||
For the same functions $f'(n)$ and $T'(n)$ defined in the proof of Theorem~4.4, we have | ||
\begin{align*} | ||
f'(n) &= f(n_0n) \\ | ||
&= \Theta((n_0n)^{\log_ba}/\lg(n_0n)) \\ | ||
&= \Theta(n^{\log_ba}/\lg n), | ||
\end{align*} | ||
since $a$, $b$, and $n_0$ are all constants. | ||
Thus, by case 2$'$ of Lemma~4.3 shown earlier, we have that the summation in equation~(4.18) of Lemma~4.2 is $\Theta(n^{\log_ba}\lg\lg n)$, yielding | ||
\begin{align*} | ||
T(n) &= T'(n/n_0) \\ | ||
&= \Theta((n/n_0)^{\log_ba})+\Theta((n/n_0)^{\log_ba}\lg\lg(n/n_0)) \\ | ||
&= \Theta(n^{\log_ba})+\Theta(n^{\log_ba}\lg\lg n) \\ | ||
&= \Theta(n^{\log_ba}\lg\lg n) && \text{(by \refProblem{3-5}(c))}. | ||
\end{align*} |